Pengaruh CRM, Fintech, dan Kepercayaan Terhadap Loyalitas Nasabah: Peran Mediasi Kepuasan pada BSI KCP Kudus - Armanda, Billy; Hana , Kharis Fadhullah (Journal of Economics and Business Research (JUEBIR), 2025)
This study aims to analyze the level of customer loyalty influenced by customer relationship marketing, fintech, and trust mediated by satisfaction at BSI KCP Kudus. This research uses quantitative methods with an associative approach. The data used is primary data, by distributing questionnaires to BSI KCP Kudus customers as many as 100 respondents determined by purposive sampling technique. The analysis method used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach with SmartPLS 4.0 software. The results showed that customer relationship marketing variables had no significant effect on customer satisfaction and loyalty, fintech variables had a significant effect on satisfaction, but had no significant effect on customer loyalty, while trust variables had a significant effect on customer satisfaction and loyalty. Then the satisfaction variable has a significant effect on customer loyalty. Satisfaction does not mediate the effect of customer relationship marketing and fintech on customer loyalty and satisfaction mediates the effect of trust on customer loyalty BSI KCP Kudus. The research findings confirm that BSI KCP Kudus can increase customer loyalty by increasing trust and satisfaction. BSI KCP Kudus must be able to increase the relevance of CRM programs and maintain the quality of fintech services.